Os credit default swaps e a sua função de cobertura de risco - Afonso, Raquel Alexandra Lourenço (2019)
The present work concerns about the development of the credit default swap contract, on a juridical-economic perspective. According to this logic, we aim to adopt a systematic approach, whereby the path taken will depart from the contextualization of the credit default swaps (historical remnant, modalities, etc), passing through the existing market regulation in which this financial instrument operates and, essentially, focusing the readers’ attention to the importance of certain international organizations, such as International Swaps and Derivatives Association (ISDA), which plays a key role in the development and supervision of these transactions, at the international practice level. Among the various types of CDS, the most relevant is the one that contrasts Corporate CDS (formed within the corporate sector) with Sovereign CDS (which mainly deals with sovereign debt). It should be noted that the scope of this study is confined to the corporate CDS, taking into consideration the substantial differences not only in the underlying materiality, but also in the level of the legal and procedural treatment. We therefore chose to limit the scope of this analysis, in accordance with a specialty logic, in order to further analyze the specificities associated to the corporate CDS. Finally, we will address the different ways of the contract’s termination, as well as the vicissitudes that may arise from it, dedicating the final part of this thesis to the conclusions we draw from our deep thoughts. Let this rehearsal begin.